2012
DOI: 10.1016/j.expneurol.2012.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Multiple mechanisms of microglia: A gatekeeper's contribution to pain states

Abstract: Microglia are gatekeepers in the CNS for a wide range of pathological stimuli and they blow the whistle when things go wrong. Collectively, microglia form a CNS tissue alarm system (Kreutzberg's "sensor of pathology"), and their involvement in physiological pain is in line with this function. However, pathological neuropathic pain is characterized by microglial activation that is unwanted and considered to contribute to or even cause tactile allodynia, hyperalgesia and spontaneous pain. Such abnormal microglia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 94 publications
1
35
0
Order By: Relevance
“…Therefore, the antinociceptive effects of ibuprofen [18,45], aspirin [40,46], and paracetamol [21,47,48] in this type of pain could be explained by their inhibition of COX-2 and ability to decrease TNF ␣ levels. It has been recently shown that ibuprofen [49], and aspirin [50] inhibit microglial activity, which could also explain their effectiveness in diabetic neuropathy, as activated microglia may be involved in the development of diabetic neuropathy [51,52]. Recent studies have suggested that the antinociception of paracetamol in neuropathic pain is mediated by cannabinoid receptors [25,53].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the antinociceptive effects of ibuprofen [18,45], aspirin [40,46], and paracetamol [21,47,48] in this type of pain could be explained by their inhibition of COX-2 and ability to decrease TNF ␣ levels. It has been recently shown that ibuprofen [49], and aspirin [50] inhibit microglial activity, which could also explain their effectiveness in diabetic neuropathy, as activated microglia may be involved in the development of diabetic neuropathy [51,52]. Recent studies have suggested that the antinociception of paracetamol in neuropathic pain is mediated by cannabinoid receptors [25,53].…”
Section: Discussionmentioning
confidence: 99%
“…Spinal microglia activation (using markers CD11b and ED1) has been observed in the early phase of neuropathic pain, 2) which is closely correlated with induction and maintenance of allodynia and hyperalgesia. 3) In line with this view, microglia inhibitors successfully alleviate neuropathic pain in experimental models. 3,4) Similar with neuropathic condition, peripheral inflammation by intraplanar zymosan injection as an experimental rheumatoid arthritis model also results in the development of hyperalgesia and allodynia accompany with spinal microglia activation and cytokine expression.…”
mentioning
confidence: 79%
“…3) In line with this view, microglia inhibitors successfully alleviate neuropathic pain in experimental models. 3,4) Similar with neuropathic condition, peripheral inflammation by intraplanar zymosan injection as an experimental rheumatoid arthritis model also results in the development of hyperalgesia and allodynia accompany with spinal microglia activation and cytokine expression. 5,6) Accumulative data have been revealed that activation of mitogen activated protein kinases (MAPKs, i.e., extracellular signal-regulated protein kinase (ERK) 1/2, p38 MAPK, and ERK5) in both spinal neurons and microglia may have a pivotal role in development of pain symptom following nerve injury and peripheral inflammation.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Therefore, the interaction of neurons and microglia cells is of special importance. Microglia cells are immune cells of the central nervous system though with different functions [7]. In healthy tissue, microglia cells are in a state commonly described as the "resting state".…”
Section: Changes In Pain Perception After Inflammation and Nerve Injurymentioning
confidence: 99%